The Impact of Advertising Campaigns on Consumers’ Purchasing Decision in Delivery Application: A Field Study on Grocery Delivery App in Saudi Arabia - Bakhashwain, Wasaef Ali; Serri, Lara Zainalabdien; Owies, Mohamed GadElmawla (Arab Journal for Sciences and Research Publishing, 2024)
The study aimed to identify the impact of advertising campaigns on the purchasing decision of consumers of delivery applications, by studying the dimensions of the advertising campaign (content of the advertising campaign, type of advertising campaign, type of promotional offers in the advertising campaign). To achieve this goal, the two researchers used the descriptive analytical approach, where a questionnaire was designed as a tool for data collection. A random sample of (277) individuals was selected. The researchers relied on (SPSS) software package for analysing data. Results showed that advertising campaigns, based on their dimensions (content of the advertising campaign, type of advertising campaign, type of promotional offers in the advertising campaign), affect the purchasing decision of consumers of food delivery applications in the Kingdom of Saudi Arabia. The study recommended the necessity of paying attention to social media posts, as they help in identifying delivery application services, and using different types of promotional offers in advertising campaigns, which helps in influencing the purchasing decision positively.
Keywords: Advertising campaigns; purchasing decisions; consumer; grocery applications